Atrial tachycardia with multiple reconductions across the surgical incision. (1st August 2020) - Nagai, Takayuki; Kawakami, Hiroshi; Sasaki, Yasuhiro; Fujii, Akira; Inoue, Katsuji; Ikeda, Shuntaro; Yamaguchi, Osamu
Abstract: Incisional atrial tachycardia (AT) with multiple penetrating points on one surgical incision has not been reported yet. We present a case of incisional AT following mitral valve annuloplasty with a superior transseptal approach, in which two reconduction sites were parts of the reentrant circuit. Radiofrequency ablation at the reconduction site successfully terminated the tachycardia. A total of four penetrating points were found on the incision line, and radiofrequency ablation at these sites was completed. Detailed mapping of possible reconduction sites along the incision line should be performed to avoid further instances of AT following open heart surgery.